Ikan kutuk abdi dewi sri: penelitian ekspedisi penelusuran legenda pembelajaran multiliterasi sd - Tasya Hasnabila Qonitatin Hafidzoh; Fida Chasanatun; Candra Candra Dewi; Eka Nofri Ari Yanto (Universitas PGRI Madiun, 2026)
Multiliteracy is one of the 21st-century skills that is crucial for elementary school students to master. Multiliteracy can be implemented by utilizing children’s stories in the form of local legends. The purpose of this study is to explore local wisdom values as the basis for formulating the plot of a local legend from the Petirtaan Dewi Sri site in Simbatan Village, Magetan Regency, as multiliteracy learning material for elementary school students. The research method used is qualitative phenomenological research employing the expedition field technique. The qualitative research was conducted through observation, interviews, and documentation. This study employed the constant comparative method while adopting a people-oriented research approach. The study utilized purposive sampling and snowball sampling as data collection methods, interviewing sources/informants with in-depth historical knowledge regarding the Petirtaan Dewi Sri site. The individuals interviewed included the site caretaker, village officials who authored historical books, the chairperson of the tourism awareness group (POKDARWIS), artists, and elders in Simbatan Village, Magetan Regency. The results of this study indicate that local folklore—particularly from the Petirtaan Dewi Sri site in Simbatan Village—contains local wisdom that can be integrated as multiliteracy learning material capable of instilling moral values in elementary school-aged children.